2006
DOI: 10.15388/stepp.2006.3.8582
|View full text |Cite
|
Sign up to set email alerts
|

The challenge of social services development – the establishment of welfare pluralism in social services

Abstract: Na uji iššūkiai socialinių paslaugų plėtrai -mišrios socialinių paslaugų rinkos kūrimas Laimutė Žalimienė Įvadas Pastaruoju dešimtmečiu socialinėje ir ekonominėje politikoje atsiranda naujos sąvokos ir koncepcijos, tokios kaip "mišri socialinių paslaugų rinka", "mišri globos ekonomika", kurios pabrėžia, kad teikiant socialines paslaugas kaip lygiaverčiai partneriai, turintys vienodas teises ir galimybes, dirba valstybės, savivaldybių, nevyriausybinių organizacijų (toliau -NVO) ar privačios įstaigos.Europos Sąj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The mediation of social workers providing social services to the elderly is understood as various functions, such as accompanying, providing information, representing, navigating for doctor's or nurse's consultation, and referral for receiving palliative care. Mediation and representation are described in the catalogue of social services, which Lithuanian social workers apply in practice [19].…”
Section: Social Work Roles and Functions In Integrated Carementioning
confidence: 99%
“…The mediation of social workers providing social services to the elderly is understood as various functions, such as accompanying, providing information, representing, navigating for doctor's or nurse's consultation, and referral for receiving palliative care. Mediation and representation are described in the catalogue of social services, which Lithuanian social workers apply in practice [19].…”
Section: Social Work Roles and Functions In Integrated Carementioning
confidence: 99%
“…Consistently, 47.9% of those entitled for long-term care benefits opt for cash-for care benefits (Lazutka et al, 2018). Care homes are commonly regarded as institutions for older people rejected by their families (Žalimienė, 2019). For this reason, the share of older adults aged 65+ residing in care homes in Lithuania has remained at around 1% since 2001.…”
Section: Introductionmentioning
confidence: 99%
“…It should be pointed out that, although social services at person's home are given priority, in Lithuania, research on the subject has not been conducted. The analysis of scientific literature revealed that scholars have drawn a great deal of attention to the problem of the quality of services [11][12][13][14], the management of social services and the effectiveness of services and the problem of the cost reduction of services [2,[16][17][18], the expression of empowerment in the context of social services [19,20]. In the context of the aforementioned studies, the problem of social services at home, as one of the priority areas of change in social services system is highlighted.…”
Section: Introductionmentioning
confidence: 99%